Quality analysis in the provision of legal services: a case study using the SWOT matrix - Santos, André de Mendonça; Silva, Natália Macêdo e (Brazilian Journal of Production Engineering, 2023)
This work aims to analyze the quality level of legal services provided by a law firm in the city of Alagoinhas-BA, seeking to identify the problems experienced, to propose improvements and to disseminate knowledge about quality concepts within the organization. For this, the present case study carried out semi-structured interviews with employees, with a descriptive and qualitative approach, and on-site visits in order to analyze the organization’s layout. The SWOT matrix and cross matrix were used for better analysis of the collected information and development of propositions. Finally, the use of technological tools was proposed, such as legal ERP, WhatsApp chatbot and Microsoft Teams, and marketing, with the intensification of disclosures on social networks and the application of the 5S concept in order to improve communication, organization, to increase productivity and customer satisfaction.